A high-strength corrosion-resistant high-entropy alloy multilayer film and a preparation method and application thereof
Patent Information
- Application Number
- CN202410231855.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-01
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-01
AI Technical Summary
[0007]针对现有技术的不足,本发明提供了一种高强耐蚀高熵合金多层膜及其制备方法与应用,具备耐磨性、耐腐蚀性能、塑性和强度高等优点,解决了现有涂层耐磨性和耐腐蚀性差,无法在高摩擦和腐蚀性的使用环境下使用的问题
[0030]与现有技术相比,本发明提供了一种高强耐蚀高熵合金多层膜及其制备方法与应用,具备以下有益效果:
Smart Images

Figure CN118007084B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of corrosion-resistant high-entropy alloy multilayer film technology, specifically relating to a high-strength corrosion-resistant high-entropy alloy multilayer film, its preparation method, and its application. Background Technology
[0002] Engineering materials need to possess both high strength and good corrosion resistance to achieve long service life under operating conditions. The development of coating technology has reduced the maintenance costs of engineering materials and improved the efficiency of immediate repair. The strength and corrosion resistance of traditional alloys are no longer sufficient to meet the service requirements of certain harsh environments. Under some extreme operating conditions, the material surface is prone to service failure due to wear and corrosion. The emergence of high-entropy alloys has opened up more possibilities for designing coatings with excellent comprehensive mechanical and corrosion resistance properties. High-entropy alloys break through the design constraints of traditional alloys, exhibiting thermodynamic high-entropy effects, kinetic hysteresis diffusion effects, structural lattice distortion effects, and a "cocktail" effect in performance, resulting in excellent corrosion resistance and comprehensive mechanical properties. However, the application of bulk high-entropy alloys is limited due to the complexity and difficulty of their preparation process. Surface technology, on the other hand, can achieve the preparation of high-performance protective high-entropy alloy coatings without affecting the intrinsic properties of the base material, thereby providing efficient protection for lower-cost base material surfaces and broadening the application areas of high-entropy alloys.
[0003] A search revealed that patent CN115961252A discloses a machine-based method for preparing corrosion-resistant amorphous alloy multilayer films. These corrosion-resistant amorphous multilayer films are obtained by dual-target magnetron sputtering deposition and consist of an extremely thin, lightweight alloy MgCuY amorphous layer embedded within a CoFeTaB amorphous alloy. They exhibit excellent corrosion resistance, specifically demonstrated by a self-corrosion potential of -0.5V and a self-corrosion current density of 2.5 × 10⁻⁶ V in NaCl solution. -6 A·cm 2 However, the corrosion resistance of the multilayer film in this technology still needs to be improved, and the resulting multilayer film has poor wear resistance and cannot be used in high-friction environments.
[0004] Patent No. CN114438489B discloses a method for preparing a wear-resistant and corrosion-resistant alloy coating. The coating is prepared by laser cladding and consists of a nickel-based anti-corrosion layer, a transition layer of nickel-based alloy and WC powder, and a WC wear-resistant layer. The coating has a hardness of 200-700 HV, but its corrosion resistance is not effectively demonstrated, which makes the alloy coating unusable in some corrosive environments.
[0005] However, friction and corrosive service environments are common in engineering applications. Therefore, in order to ensure the performance of engineering materials in such environments, it is urgent to design a high-strength, corrosion-resistant, high-entropy alloy multilayer film and its preparation method, so as to prepare a high-strength, corrosion-resistant, high-entropy alloy multilayer film structure that can be used in such environments to protect engineering materials, thereby solving the problems of the existing technology. Summary of the Invention
[0006] (a) Technical problems to be solved
[0007] To address the shortcomings of existing technologies, this invention provides a high-strength, corrosion-resistant, high-entropy alloy multilayer film, its preparation method, and its application. This film possesses advantages such as wear resistance, corrosion resistance, plasticity, and high strength, solving the problem that existing coatings have poor wear and corrosion resistance and cannot be used in high-friction and corrosive environments.
[0008] (II) Technical Solution
[0009] To achieve the above-mentioned objective of preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film with high wear resistance, corrosion resistance, plasticity, and strength, the present invention provides the following technical solution:
[0010] A method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film, which is based on magnetron sputtering technology to prepare a coating on a substrate, including...
[0011] Step 1. Treat the substrate to remove impurities from its surface, and then fix the substrate onto the sample tray;
[0012] Step 2. Use nitrogen to break the vacuum in the vacuum chamber, install the sample tray and the two targets Cr and NbMoTaCr respectively, and evacuate the sputtering chamber.
[0013] Step 3. Open the argon gas valve, the pneumatic switch of the argon gas filling valve, and the diaphragm gauge protection valve; adjust the gate valve opening, the working gas pressure of the resistance gauge, and the working gas pressure of the diaphragm gauge.
[0014] Step 4. Connect the target materials to two DC power supplies respectively, set the sputtering power of Cr target to 100-120W, the sputtering power of NbMoTaCr target to 140-160W, and the substrate bias voltage to -70--90V;
[0015] Step 5. Sputter the substrate to prepare a high-strength, corrosion-resistant, high-entropy alloy multilayer film on the substrate surface;
[0016] Step 6. After sputtering is complete, close the thin film gauge protection valve, turn off the power supply to both targets and the argon gas valve, and allow the sample to cool to room temperature in the chamber before removing the sample.
[0017] Preferably, the substrate treatment process in step 1 includes:
[0018] The substrate was ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water for 10–20 minutes at an ultrasonic frequency of 60–90 Hz, and then dried in a vacuum drying oven.
[0019] Preferably, step 2, the process of evacuating the sputtering chamber, includes using a mechanical pump to evacuate the sputtering chamber to a vacuum level of 0–10 Pa, then turning on a molecular pump to continue evacuating the vacuum level to the target vacuum level of 5 × 10 Pa. -5 ~5×10 -4 Pa.
[0020] Preferably, the argon flow rate in step 3 is 20-30 sccm, the gate valve opening is 10%-20%, the working pressure of the resistance gauge is 0.3-0.5 Pa, and the working pressure of the diaphragm gauge is 1.0-2.0 Pa.
[0021] Preferably, the process of preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film on the substrate surface in step 5 includes:
[0022] Step 51. Set the sample disk rotation speed to 15-17 rpm. Under the premise that the target baffle and sample baffle are not open, pre-sputter the two targets for 10-20 min each. Then, open the Cr target baffle and sample baffle first, sputter the Cr layer for 10-15 min, then close the Cr target baffle, open the NbMoTaCr target baffle, and sputter the NbMoTaCr layer for 9-13 min.
[0023] Step 52. Perform three cycles of co-sputtering to form a high-strength, corrosion-resistant, high-entropy alloy multilayer film on the substrate surface.
[0024] A high-strength, corrosion-resistant, high-entropy alloy multilayer film is disclosed, comprising several Cr layers and NbMoTaCr layers, wherein the Cr layers and NbMoTaCr layers are spaced apart, and the bottom Cr layer is in contact with the substrate as the bottom layer, and the outermost layer is an NbMoTaCr layer; the film thickness ratio of the Cr layer to the NbMoTaCr layer is 1:1, the thickness of a single Cr layer or NbMoTaCr layer is 120-170 nm, and the total film thickness is 700-1000 nm;
[0025] The high-strength, corrosion-resistant, high-entropy alloy multilayer film was prepared using a method for preparing high-strength, corrosion-resistant, high-entropy alloy multilayer films.
[0026] Preferably, the NbMoTaCr layer comprises three Cr layers and three NbMoTaCr layers.
[0027] Preferably, the high-strength, corrosion-resistant, high-entropy alloy multilayer film has a nanoindentation hardness of 7–8 GPa, an elastic modulus of 140–150 GPa, and a corrosion potential of -0.20 to -0.26 V and a strength of 1.0–5.0 × 10⁻⁶ V in a 3.5 wt.% NaCl solution.-6 A·cm -2 Corrosion current density.
[0028] An application of a high-strength, corrosion-resistant, high-entropy alloy multilayer film: The Cr / NbMoTaCr multilayer film not only has good bonding with the substrate but also possesses strong plasticity and corrosion resistance. It has broad application prospects under extreme service conditions in hydraulic and marine engineering, such as wear resistance and corrosion prevention. It can achieve effective protection of the surface of steel structure materials and efficient and long-life service of engineering components, providing wear-resistant and corrosion-resistant protection for the surface of steel structure materials under extreme service conditions in hydraulic and marine engineering.
[0029] (III) Beneficial Effects
[0030] Compared with the prior art, the present invention provides a high-strength, corrosion-resistant, high-entropy alloy multilayer film, its preparation method, and its application, which have the following beneficial effects:
[0031] 1. This invention presents a method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film based on magnetron sputtering technology. This method involves depositing a Cr metal layer followed by an NbMoTaCr high-entropy alloy layer on a polished stainless steel substrate using magnetron sputtering, with a thickness ratio of 1:1. This process is repeated three times, resulting in six layers. The deposited coating is dense, uniform, smooth, and exhibits excellent film-substrate adhesion. This multilayer film system prepared using magnetron sputtering technology can provide wear-resistant and corrosion-resistant protection for the stainless steel substrate.
[0032] 2. This invention prepares a wear-resistant and corrosion-resistant alloy coating by means of a high-strength, corrosion-resistant, high-entropy alloy multilayer film based on magnetron sputtering technology. A Cr layer serves as the underlayer to improve the adhesion between the coating and the substrate, while also effectively enhancing the overall corrosion resistance and plasticity of the coating. The NbMoTaCr layer effectively improves the overall strength and corrosion resistance of the coating. Simultaneously, the coating exhibits a nano-indentation hardness of 7–8 GPa, an elastic modulus of 140–150 GPa, and a corrosion potential of -0.20 to -0.26 V and a strength of 1.0–5.0 × 10⁻⁶ V in a 3.5 wt.% NaCl solution. -6 A·cm -2 With a high corrosion current density, it features high wear resistance and high corrosion resistance, ensuring the performance of engineering materials in high friction and corrosive environments. Attached Figure Description
[0033] Figure 1 This is the XRD pattern of the high-strength, corrosion-resistant, high-entropy alloy multilayer film of the present invention.
[0034] Figure 2 The images show the SEM morphology and thickness of the high-strength, corrosion-resistant, high-entropy alloy multilayer film of this invention.
[0035] Figure 3 This is an EDS-area scan distribution diagram of the Cr / NbMoTaCr multilayer film of the present invention.
[0036] Figure 4 These are typical nanoindentation load-displacement curves at different test points of the Cr / NbMoTaCr multilayer film of this invention.
[0037] Figure 5 This is a typical nanoindentation hardness and elastic modulus diagram at different test points of the Cr / NbMoTaCr multilayer film of this invention.
[0038] Figure 6 This is a potentiodynamic polarization curve of the Cr / NbMoTaCr multilayer film of the present invention in a 3.5 wt.% NaCl solution. Detailed Implementation
[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] Example 1: Preparation process of high-strength, corrosion-resistant, high-entropy alloy multilayer film
[0041] Please see Figures 1-6 This invention provides a technical solution: a method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film. In this embodiment, the method uses a Pengcheng Vacuum CK450 ultra-high vacuum three-target magnetron sputtering deposition system to prepare the coating. The coating substrates are (100) single-polished silicon wafers and 304 stainless steel. The coating samples on the silicon substrate are used for materials characterization and mechanical property testing, while the coating samples on the 304 stainless steel substrate are used for electrochemical testing.
[0042] Example 1. A method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film, comprising:
[0043] Step 1. Clean the two substrates, (100) silicon wafer and 304 stainless steel disc, with acetone, anhydrous ethanol and deionized water for 10 minutes respectively. The ultrasonic frequency is 70Hz to remove grease and impurities from the surface of the substrates. Then dry them in a vacuum drying oven. Then stick the two substrates to the sample tray with high temperature resistant tape.
[0044] Step 2. Break the vacuum in the vacuum chamber using nitrogen gas, install the sample tray and the two targets (Cr and NbMoTaCr), and evacuate the sputtering chamber. After evacuating the sputtering chamber to a vacuum level of 3 Pa using a mechanical pump, turn on the molecular pump and continue evacuating to the target vacuum level of 5 × 10⁻⁶ Pa.-5 Pa;
[0045] Step 3. Open the gas valve on the argon cylinder, set the argon flow rate to 20 sccm in the program, open the pneumatic switch of the argon filling valve, open the diaphragm gauge protection valve, adjust the gate valve opening to 10%, the resistance gauge displays the working gas pressure as 0.3 Pa, and the diaphragm gauge displays the working gas pressure as 1.0 Pa.
[0046] Step 4. Connect the target to two DC power supplies respectively, set the sputtering power of Cr target to 100W, the sputtering power of NbMoTaCr target to 140W, and the substrate bias voltage to -70V.
[0047] Step 5. Set the sample disk rotation speed to 15 rpm. Under the premise that the target baffle and the sample baffle are not open, pre-sputter the two targets for 10 min each. Then, open the Cr target baffle and the sample baffle first, and sputter the Cr layer for 11 min. Then, close the Cr target baffle, open the NbMoTaCr target baffle, and sputter the NbMoTaCr layer for 10 min. Sputter for a total of 3 cycles.
[0048] Step 6. After sputtering is complete, close the thin film gauge protection valve, turn off the power supply to both targets and the argon valve, and allow the sample to cool to room temperature in the chamber before removing the sample to prevent sample oxidation.
[0049] Step 7. In the deposited Cr / NbMoTaCr multilayer film, both the NbMoTaCr layer and the Cr layer have a BCC structure (e.g., Figure 1 As shown in the XRD pattern, the Cr to NbMoTaCr layer thickness ratio is 1:1, the single-layer thickness is 150 nm, and the total film thickness is 900 nm (as shown in the XRD pattern). Figure 2 The SEM morphology of the multilayer film is shown in the figure. The elements in each layer are uniformly distributed (e.g., Figure 3 (The surface scan distribution of the EDS energy dispersive spectroscopy of the multilayer film is shown in the figure); the multilayer film has a nanoindentation hardness of 7.9 GPa, an elastic modulus of 148.2 GPa, a corrosion potential of -0.20 V and a strength of 1.0 × 10⁻⁶ in a 3.5 wt.% NaCl solution. -6 A·cm -2 Corrosion current density.
[0050] Example 2: A method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film, including...
[0051] Step 1. Clean the two substrates, (100) silicon wafer and 304 stainless steel disc, with acetone, anhydrous ethanol and deionized water for 15 minutes respectively. The ultrasonic frequency is 80Hz to remove grease and impurities from the surface of the substrates. Then dry them in a vacuum drying oven. Then use high temperature resistant tape to stick the two substrates firmly to the sample tray.
[0052] Step 2. Break the vacuum in the vacuum chamber using nitrogen gas, install the sample tray and the two targets (Cr and NbMoTaCr), and evacuate the sputtering chamber. After evacuating the sputtering chamber to a vacuum level of 5 Pa using a mechanical pump, turn on the molecular pump and continue evacuating to the target vacuum level of 1 × 10⁻⁶ Pa. -5 Pa;
[0053] Step 3. Open the gas valve on the argon cylinder, set the argon flow rate to 25 sccm in the program, open the pneumatic switch of the argon filling valve, open the diaphragm gauge protection valve, adjust the gate valve opening to 12%, the resistance gauge displays the working gas pressure as 0.4 Pa, and the diaphragm gauge displays the working gas pressure as 1.5 Pa.
[0054] Step 4. Connect the target to two DC power supplies respectively, set the sputtering power of Cr target to 110W, the sputtering power of NbMoTaCr target to 160W, and the substrate bias voltage to -80V.
[0055] Step 5. Set the sample disk rotation speed to 16 rpm. Under the premise that the target baffle and the sample baffle are not open, pre-sputter the two targets for 15 min each. Then, open the Cr target baffle and the sample baffle first, and sputter the Cr layer for 13 min. Then, close the Cr target baffle, open the NbMoTaCr target baffle, and sputter the NbMoTaCr layer for 11 min. Sputter for a total of 3 cycles.
[0056] Step 6. After sputtering is complete, close the thin film gauge protection valve, turn off the power supply to both targets and the argon valve, and allow the sample to cool to room temperature in the chamber before removing the sample to prevent sample oxidation.
[0057] Step 7. In the deposited Cr / NbMoTaCr multilayer film, both the NbMoTaCr and Cr layers have a BCC structure, with a Cr to NbMoTaCr layer thickness ratio of 1:1, a single layer thickness of 140 nm, and a total film thickness of 840 nm. The multilayer film exhibits a nanoindentation hardness of 7.7 GPa and an elastic modulus of 145.4 GPa (e.g., ...). Figure 4 and Figure 5 The nanoindentation test results show that it has a corrosion potential of -0.23 V and 3.0 × 10⁻⁶ Ω·cm in a 3.5 wt.% NaCl solution. -6 A·cm -2 Corrosion current density.
[0058] Example 3: A method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film, including...
[0059] Step 1. Clean the two substrates, (100) silicon wafer and 304 stainless steel disc, with acetone, anhydrous ethanol and deionized water for 20 minutes respectively. The ultrasonic frequency is 90Hz to remove grease and impurities from the surface of the substrates. Then dry them in a vacuum drying oven. Then use high temperature resistant tape to firmly stick the two substrates to the sample tray.
[0060] Step 2. Break the vacuum in the vacuum chamber using nitrogen gas, install the sample tray and the two targets (Cr and NbMoTaCr), and evacuate the sputtering chamber. After evacuating the sputtering chamber to a vacuum level of 10 Pa using a mechanical pump, turn on the molecular pump and continue evacuating to the target vacuum level of 5 × 10 Pa. -4 Pa;
[0061] Step 3. Open the gas valve on the argon cylinder, set the argon flow rate to 30 sccm in the program, open the pneumatic switch of the argon filling valve, open the diaphragm gauge protection valve, adjust the gate valve opening to 16%, the resistance gauge displays the working gas pressure as 0.5 Pa, and the diaphragm gauge displays the working gas pressure as 2.0 Pa.
[0062] Step 4. Connect the target to two DC power supplies respectively, set the sputtering power of Cr target to 120W, the sputtering power of NbMoTaCr target to 160W, and the substrate bias voltage to -90V.
[0063] Step 5. Set the sample disk rotation speed to 17 rpm. Under the premise that the target baffle and the sample baffle are not open, pre-sputter the two targets for 20 min each. Then, open the Cr target baffle and the sample baffle first, and sputter the Cr layer for 15 min. Then close the Cr target baffle, open the NbMoTaCr target baffle, and sputter the NbMoTaCr layer for 13 min. Sputter for a total of 3 cycles.
[0064] Step 6. After sputtering is complete, close the thin film gauge protection valve, turn off the power supply to both targets and the argon valve, and allow the sample to cool to room temperature in the chamber before removing the sample to prevent sample oxidation.
[0065] Step 7. In the deposited Cr / NbMoTaCr multilayer film, both the NbMoTaCr and Cr layers have a BCC structure, with a Cr to NbMoTaCr layer thickness ratio of 1:1, a single layer thickness of 165 nm, and a total film thickness of 990 nm. The multilayer film exhibits a nanoindentation hardness of 7.8 GPa, an elastic modulus of 148.1 GPa, a corrosion potential of -0.22 V in a 3.5 wt.% NaCl solution, and a corrosion potential of 5.0 × 10⁻⁶. -6 A·cm -2 Corrosion current density (e.g.) Figure 6 (As shown in the potentiodynamic polarization curve).
[0066] Through the above three examples, the high-strength, corrosion-resistant, high-entropy alloy multilayer film prepared in Example 1 has relatively better comprehensive mechanical properties and corrosion resistance, as shown in Table 1.
[0067] Table 1: Properties of high-strength and corrosion-resistant Cr / NbMoTaCr multilayer films prepared in Examples 1-3
[0068]
[0069]
[0070] Example 2: Unlike the method described in Example 1, this example provides a comparative scheme:
[0071] Comparative Example 1: Utilizing the corrosion-resistant amorphous alloy multilayer film preparation method disclosed in patent number CN115961252A, a corrosion-resistant amorphous alloy multilayer film was formed by embedding an extremely thin light alloy MgCuY amorphous layer into a CoFeTaB amorphous alloy using dual-target magnetron sputtering. The corrosion resistance was significantly improved compared to the pure CoFeTaB amorphous film, and the introduced heterogeneous interface served as a diffusion barrier for corrosive substances and cracks. The self-corrosion potential of this multilayer film was -0.51V, and the self-corrosion current density was 2.51 × 10⁻⁶. -6 A·cm -2 However, this invention does not demonstrate the mechanical properties of amorphous alloy multilayer films, and their corrosion resistance still needs further improvement.
[0072] Comparative Example 2: Using the impeller corrosion-resistant coating preparation method disclosed in patent number CN115351271A, a single-component BCC structure corrosion-resistant coating with Ni, Cr, Mo, Co, Cu, W, Nb, Al, Ti, and rare earth oxides was obtained by supersonic flame spraying and strengthening treatment. This coating exhibits certain microhardness and bonding strength, and is resistant to 5% neutral salt spray and 5% sulfuric acid corrosion, showing no bubbles or oxidation after 72 hours. However, the coating in this invention does not demonstrate the coating's inherent strength and corrosion resistance indicators.
[0073] Comparative Example 3: A method for preparing a high-strength wear-resistant and corrosion-resistant composite coating on the surface of low-carbon steel, as disclosed in patent number CN109487268A, was used. This method employed a combination of induction cladding, electrode heating heat treatment, and nitriding to prepare the high-strength wear-resistant and corrosion-resistant composite coating on the low-carbon steel surface. The bottom layer of the coating is a cladding layer formed by a mixed coating of rare earth elements, graphene, and Ni-based materials; the middle layer consists of porous ceramic and hard ceramic layers; and the top layer is a nitrided layer. The surface hardness of the coating is 62.3 HRC, and the corrosion current density in a 3.5 wt.% NaCl solution is 1.25 × 10⁻⁶. -4 A·cm -2 .
[0074] Comparative Example 4: Using a method for preparing a corrosion-resistant and erosion-resistant multifunctional coating disclosed in patent number CN116213227B, a buffer coating (polydimethylsiloxane, polyurethane, or epoxy resin) and a curing agent (vinyltriamine, diaminodiphenylmethane, or adipate dihydrazide) were coated onto a steel substrate using a spin coating method to obtain a corrosion-resistant and erosion-resistant multifunctional coating with a corrosion current density of 2.15 × 10⁻⁶. -5 A·cm -2 The sustained-release rate is 85%.
[0075] The comparison is shown in Table 2;
[0076] Table 2: Comparison of Coating Performance
[0077]
[0078] As can be seen from the comparative examples shown in Table 2, the high-strength, corrosion-resistant, high-entropy alloy multilayer film prepared by the method described in Example 1 of this invention has relatively superior comprehensive mechanical and corrosion resistance properties, and can effectively protect the surface of hydraulic and marine steel components from corrosion and wear. Moreover, the Cr / NbMoTaCr multilayer film not only has good bonding with the substrate, but also has strong plasticity and corrosion resistance, and has broad application prospects under extreme service conditions in hydraulic and marine engineering such as wear resistance and corrosion resistance. It can effectively protect the surface of steel structure materials and achieve efficient and long-life service of engineering components, and can be used to provide wear-resistant and corrosion-resistant protection for the surface of steel structure materials under extreme service conditions in hydraulic and marine engineering.
[0079] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0080] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film, characterized in that: This method is based on magnetron sputtering technology to prepare coatings on a substrate, including Step 1. Treat the substrate to remove impurities from its surface, and then fix the substrate onto the sample tray; Step 2. Use nitrogen to break the vacuum in the vacuum chamber, install the sample tray and the two targets, Cr and NbMoTaCr, respectively, and evacuate the sputtering chamber. Step 3. Open the argon gas valve, the pneumatic switch of the argon gas filling valve, and the diaphragm gauge protection valve; adjust the gate valve opening, the working gas pressure of the resistance gauge, and the working gas pressure of the diaphragm gauge. Step 4. Connect the target materials to two DC power supplies respectively, set the sputtering power of Cr target to 100~120 W, the sputtering power of NbMoTaCr target to 140~160 W, and the substrate bias voltage to -70~-90 V; Step 5. Sputter the substrate to prepare a high-strength, corrosion-resistant, high-entropy alloy multilayer film on the substrate surface; Step 5 describes the process of preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film on the substrate surface, which includes... Step 5.
1. Set the sample disk rotation speed to 15~17 rpm. Under the premise that the target baffle and sample baffle are not opened, pre-sputter the two targets for 10~20 min each. Then, first open the Cr target baffle and sample baffle and sputter the Cr layer for 10~15 min. Then close the Cr target baffle, open the NbMoTaCr target baffle, and sputter the NbMoTaCr layer for 9~13 min. Step 5.
2. Perform three cycles of co-sputtering to form a high-strength, corrosion-resistant, high-entropy alloy multilayer film on the substrate surface; Step 6. After sputtering is complete, close the thin film gauge protection valve, turn off the power supply to both targets and the argon valve, and allow the sample to cool to room temperature in the chamber before removing the sample. The high-strength, corrosion-resistant, high-entropy alloy multilayer film prepared by the above preparation method includes several Cr layers and NbMoTaCr layers. The Cr layers and NbMoTaCr layers are spaced apart, and the bottom Cr layer is in contact with the substrate as the bottom layer. The outermost layer is an NbMoTaCr layer. The film thickness ratio of the Cr layer to the NbMoTaCr layer is 1:
1. The thickness of a single Cr layer or NbMoTaCr layer is 120~170 nm, and the total film thickness is 700~1000 nm. The Cr / NbMoTaCr multilayer film consists of three Cr layers and three NbMoTaCr layers. The high-strength, corrosion-resistant, high-entropy alloy multilayer film has a nanoindentation hardness of 7-8 GPa, an elastic modulus of 140-150 GPa, and exhibits a corrosion potential of -0.20 to -0.26 V and a strength of 1.0-5.0 × 10⁻⁶ V in a 3.5 wt.% NaCl solution. -6 A·cm -2 Corrosion current density.
2. The method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film as described in claim 1, characterized in that: The substrate treatment process described in step 1 includes The substrate was ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water for 10-20 minutes at an ultrasonic frequency of 60-90 Hz, and then dried in a vacuum drying oven.
3. The method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film as described in claim 1, characterized in that: Step 2 describes the process of evacuating the sputtering chamber, which involves using a mechanical pump to evacuate the chamber to a vacuum level of 0-10 Pa, then turning on a molecular pump to continue evacuating the chamber to the target vacuum level of 5 × 10 Pa. -5 ~5×10 -4 Pa.
4. The method for preparing a high-strength, corrosion-resistant, high-entropy alloy multilayer film as described in claim 1, characterized in that: In step 3, the argon flow rate is 20~30 sccm, the gate valve opening is 10%~20%, the resistance gauge working pressure is 0.3~0.5 Pa, and the diaphragm gauge working pressure is 1.0~2.0 Pa.
5. An application of a high-strength, corrosion-resistant, high-entropy alloy multilayer film, characterized in that: Used to provide wear-resistant and corrosion-resistant protection for the surface of steel structure materials under extreme service conditions in hydraulic and marine engineering; The high-strength, corrosion-resistant, high-entropy alloy multilayer film is as described in any one of claims 1-4.
Citation Information
Patent Citations
Method for preparing high-strength wear-resistant corrosion-resistant composite coating on surface of low-carbon steel
CN109487268A
High-hardness erosion-resistant and abrasion-resistant composite coating, preparation method and application
CN109609905A
Multilayer protective coating with high-temperature steam oxidation resistance and hot water corrosion resistance and preparation method and application
CN110484889A
Alloy and nuclear reactor component with alloy coating on surface
CN114774756A